GEOMORPHOLOGICAL MAPPING OF THE CLARO AND BOIS RIVERS DRAINAGE BASIN USING TECHNIQUES OF REMOTE SENSING AND GEOPROCESSING - Carvalho, Thiago Morato de (Geoambiente On-line, 2013)
O objetivo deste estudo é a aplicação de técnicas de sensoriamento remoto e geoprocessamento como ferramentas auxiliares em estudos geomorfológicos. Foi utilizado como modelo de estudo o mapeamento das unidades geomorfológicas do rio Claro e rio dos Bois, ambos na mesma bacia hidrográfica localizada na margem direita do rio Araguaia, Estado de Goiás. Foram utilizadas imagens interferométricas da Shuttle Radar Topography Mission (SRTM), aplicadas numa área de 123.276 km² da bacia de drenagem dos rios Claro e Bois, cujas características geomorfológicas foram mapeadas na escala 1:100.000. Foram identificadas e caracterizadas unidades geomorfológicas denudacionais, SRAIVC1, SRAIVC2, SRAIIB-RT, SRAIIIA, HBED, ZER e MC; e unidades geomorfológicas agradacionais, faixa aluvial (FA), e unidade associada a sistemas lacustres. Abstract The aim of this study is the application of techniques of remote sensing and geoprocessing as auxiliary tools in geomorphological studies. It was used as model of study mapping the geomorphological units of the Rio Claro and Rio dos Bois, both in the basin located in the right margin of the Araguaia River, state of Goiás. It was used interferometric images of the Shuttle Radar Topography Mission (SRTM), applied for an area of 123.276 km² of the drainage of the Claro and Bois Rivers, whose geomorphological features was mapped in a scale of 1:100.000. It was identified and characterized denudational geomorphological features, the SRAIVC1, SRAIVC2, SRAIIB-RT, SRAIIIA, HB-ED, ZER, MC; and agradational geomorphological features, alluvial belts, and unit association with lake systems. Key words: geomorphology, remote sensing, SRTM, Claro and Bois Rivers.